Appropriateness of advanced upper limb prosthesis prescription for a patient with cognitive impairment: a case report. (18th August 2017) - Barredo, Jennifer; Acluche, Frantzy; Disla, Roxanne; Fantini, Christopher; Fishelis, Leah; Sasson, Nicole; Resnik, Linda
Abstract: Purpose: To describe a participant with scapulo-thoracic amputation and cognitive impairment trained to use the DEKA Arm and discuss factors relevant to the determination that he was not an appropriate candidate for independent home use of the device. Method : The participant underwent 40 h of in-laboratory training with the DEKA Arm Advanced Upper Limb Prosthesis. Pre-training neuropsychological measures of cognition were collected. Qualitative and quantitative data related to functional performance, quality of life and pain were collected after 10 h of training, and at the conclusion of training. Using a constant comparative approach, data were binned into major themes; elements within each theme were identified. Results: Six themes were relevant to the determination that the participant was inappropriate for home use of the DEKA Arm: physical and mental health; learning, memory and cognition; adult role function; functional performance; user safety and judgement and capacity for independent device use. Issues contraindicating unsupervised device use included: uncontrolled health symptoms, poor knowledge application, safety concerns, absenteeism and performance degradation under stress. Conclusion: The findings have implications for training with and prescription of the DEKA Arm and other complex upper limb prostheses. Further research is needed to develop a model to guide prescription of technologically complex upper limb prostheses. Implications for Rehabilitation: Advanced upper limb prostheses, like the DEKA Arm, promise greater functionality, but also may be cognitively demanding, raising questions of when, and if, prescription is appropriate for patients with cognitive impairment. At this time, no formal criteria exist to guide prescription of advanced upper limb prostheses. Each clinical team applies their own informal standards in decision-making. In this case report, we described six factors that were considered in determining whether or not a research participant, with scapulo-thoracic amputation and cognitive impairment was appropriate for home use of a complex upper limb prosthesis. The findings have implications for training with and prescription of the DEKA Arm, and highlights the need for further research to develop prescription guidelines for advanced assistive devices.